Why deinstitutionalisation still matters: Reclaiming a contested horizon in global mental health - Cristian Montenegro; Felipe Szabzon; Sofía Bowen; Delia da Mosto (PLOS Mental Health, 2026)
Psychiatric deinstitutionalisation (PDI) has re-emerged as an important concern in global mental health in response to the persistence of long-term institutionalisation and human rights abuses in institutions. However, contemporary responses continue to frame reform largely in managerial and technocratic terms, prioritising service coverage, bed reductions, workforce expansion, and scalability. We argue that this framing narrows the meaning of reform and its capacity to address the institutional, political, and social conditions through which psychiatric care is organised. Drawing on critical perspectives on PDI and experiences from South America, we show how PDI has developed through distinct relationships between institutional transformation, democratisation, social mobilisation, and citizenship. These trajectories illuminate contemporary dilemmas such as transinstitutionalisation, fragmented systems of care, and the persistence of segregationist and custodial logics within community settings. We propose three lenses for re-engaging with PDI as an ongoing political and ethical project: attending to context and history, decentring dominant geographies of reform, and foregrounding lived experience. Together, these lenses shift attention towards the sites where reform is actually produced—across research, policy, training, activism, and governance— and highlight the contribution of South American experiences to ongoing debates on institutional transformation.